PC (Polystyrene Concrete) - Mohd Mustafa Al-Bakri, Abdullah (Malaysian Invention and Design Society (MINDS), 2010)
Mohd Mustafa al-Bakri Abdullah and his team won silver at 18th International Invention, Innovation & Technology Exhibition (ITEX 2007), 18th - 20th July 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.